Land subsidence exposed: The impact on house prices in the Netherlands - Yashvant R. Premchand; Henri L. F. de Groot; Thomas de Graaff; Eric Koomen (Tinbergen Institute, 2024)
Land subsidence which is primarily driven by water management practices and enhanced by increasing droughts is a growing global concern that affects the environment, infrastructure, and housing. In the Netherlands, subsidence damages houses and their foundations, resulting in high costs of repair for homeowners. However, public awareness remains limited about individual vulnerability and financial impact. This study aims to identify the link between land subsidence and house prices. Using over 100,000 housing transactions from 2000-2022 and detailed subsidence data, we find an average price discount of 2.3-5.0% for houses exposed to land subsidence, with larger effects for houses constructed before 1970 for which foundation damage is more prominent. Our findings suggest that, even with limited information and low societal urgency, homebuyers do consider the potential damage of land subsidence in expressing their willingness to pay for a house, especially after recent droughts.
Keywords: Q54; R11; R14; R21; R31; 330; Land subsidence; Water management; House prices; Hedonic pricing; Climate adaptation